Singaporeans' perception of leadership in business organizations. - Ng, Hui Lin. (2008)
A study on the applicability of motivational and leadership theories in the local context, with mainly the Path goal theory in mind. The study is hoped to the starting pointing of future researches that can improve the local workforce's working conditions, efficiency and effectiveness.